Synthesis and thermal studies of solid state 2-chloro- benzylidenepyruvic acid and its compounds with sodium, aluminium (III), gallium (III) and indium (III) cations - Bannach, Gilbert; Schnitzler, Egon; Melios, Cristo Bladimiros; Ionashiro, Massao (Eclética Química, 2004)
The synthesis of sodium 2-chlorobenzylidenepyruvate and its corresponding acid as well as binary, binary together with it’s acid or hydroxo-2-chorobenzylidenepyruvate of aluminium (III), gallium (III) and indium (III), were isolated. Chemical analysis, thermogravimetry, derivative thermogravimetry (TG/DTG), simultaneous thermogravimetry-differential thermal analysis (TG-DTA) and X-ray powder diffractometry have been employed to characterize and to study the thermal behaviour of these compounds. The results provided information concerning the stoichiometry, crystallinity, thermal stability and thermal decomposition.